2020 IEEE/RSJ International Conference on Intelligent Robots and Systems (IROS) 2020
DOI: 10.1109/iros45743.2020.9341157
|View full text |Cite
|
Sign up to set email alerts
|

Learning Accurate and Human-Like Driving using Semantic Maps and Attention

Abstract: This paper investigates how end-to-end driving models can be improved to drive more accurately and humanlike. To tackle the first issue we exploit semantic and visual maps from HERE Technologies and augment the existing Drive360 dataset with such. The maps are used in an attention mechanism that promotes segmentation confidence masks, thus focusing the network on semantic classes in the image that are important for the current driving situation. Human-like driving is achieved using adversarial learning, by not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 46 publications
0
16
0
Order By: Relevance
“…It is demonstrated that our proposed method achieves a much shorter network inference time comparing to [5], as shown in Section IV-E. Moreover, to further improve the performance, similar to recent works [12], [13], we introduce a spatial attention module in our network design. The heatmap estimated by the attention module provides us a tool for visualizing and reasoning critical objects in the environment and reveals a causal relationship between them and the ego vehicle, as shown in Figure 10.…”
Section: Introductionmentioning
confidence: 78%
See 1 more Smart Citation
“…It is demonstrated that our proposed method achieves a much shorter network inference time comparing to [5], as shown in Section IV-E. Moreover, to further improve the performance, similar to recent works [12], [13], we introduce a spatial attention module in our network design. The heatmap estimated by the attention module provides us a tool for visualizing and reasoning critical objects in the environment and reveals a causal relationship between them and the ego vehicle, as shown in Figure 10.…”
Section: Introductionmentioning
confidence: 78%
“…1) Imitation Learning: Imitation Learning for motion planning was first introduced in the pioneering work [14] where it directly learns a policy that maps sensor data to steering angle and acceleration. In recent years, there is an extensive literature [15], [16], [17], [18], [19], [3], [12] that follows this end-to-end philosophy. Alternatively, our work adopts a mid-to-mid approach [5], [6] which allows us to augment data handily and go beyond pure imitation by having task-specific losses.…”
Section: Related Workmentioning
confidence: 99%
“…[11] creates a multi-camera system that can offer data for a 360-degree view of the vehicle's surroundings. Furthermore, [12] uses semantic segmentation technology to improve the perception of the environment. [13] uses semantic segmentation technology while adding geometry and motion with computer vision.…”
Section: Related Workmentioning
confidence: 99%
“…Even though nowadays, most autonomous driving (AD) stacks [30,48] use individual modules for perception, planning and control, end-to-end approaches have been proposed since the 80's [35] and the success of deep learning brought them back into the research spotlight [5,50]. Numerous works have studied different network architectures for this task [3,16,52], yet most of these approaches use supervised learning with expert demonstrations, which is known to suffer from covariate shift [36,40]. While data augmentation based on view synthesis [2,5,35] can partially alleviate this issue, in this paper, we tackle the problem from the perspective of expert demonstrations.…”
Section: Introductionmentioning
confidence: 99%